Estimating the global oceanic net freshwater flux from Argo and comparing it with satellite‐based freshwater flux products. Issue 11 (21st November 2014) - Ren, Li; Hackert, Eric; Arkin, Phillip; Busalacchi, Antonio J.
Abstract Following the idea that analysis of in situ information in the salt budget could be used as a surrogate for global "ocean rain gauge, " the annual mean oceanic net freshwater flux (E‐P) was estimated from the Argo profiles and the wind stress data on a global scale. The comparison between the independent E‐P estimation from Argo and the E‐P product sets, including the combination of precipitation from TRMM, GPCP, CMAP and evaporation from OAFlux, GSSTF3 and IFREMER and E‐P set from NEWS formed from satellite, generally show similar spatial patterns, particularly on the large scale. However, there are differences among the different satellite‐based E‐P estimates and between satellite estimates and independent in situ estimates. Based on the pattern correlation and the RMSD, the evaporation and precipitation from OAFlux and TRMM agrees best with the E‐P estimated from the independent Argo‐based estimates.